Impact of Training and Development Programs on Employee Performance in the Manufacturing Sector - Herjuna, Silvester Adi Surya; Marhaeni, Vindy Fitriawaty; Alvira, Mila; Putri, Faiqah; Anastasya, Fiona (Acta Psychologia, 2024)
This research examines the impact of training and development programs on employee performance within the manufacturing sector. By exploring the relationship between targeted training initiatives and various performance outcomes, such as productivity, job satisfaction, and safety, the study highlights the critical role of well-structured training in enhancing employee capabilities. The research also emphasizes the importance of motivation, organizational support, and customized training to address the specific needs of employees in different roles. Using a combination of qualitative and quantitative methods, including surveys and performance data analysis, the findings suggest that effective training programs lead to improved performance and higher employee retention. The study provides practical implications for manufacturing companies, urging them to prioritize training as a strategic investment and to cultivate a continuous learning culture that aligns with both organizational goals and employee development. This research contributes to the broader understanding of how training programs can be optimized to boost employee performance and organizational success in the manufacturing industry.